2005
DOI: 10.1097/01.gim.0000159901.98315.fe
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes about genetic testing and genetic testing intentions in African American women at increased risk for hereditary breast cancer

Abstract: Purpose: To evaluate attitudes about the benefits, limitations, and risks of genetic testing for BRCA1 and BRCA2 (BRCA1/2) mutations and explore testing intentions in African American women at increased risk for hereditary breast cancer. Methods: Attitudes and intentions were evaluated by telephone in African American women (n ϭ 74) at moderate and high risk for having a BRCA1/2 mutation. Results: Attitudes about the benefits of genetic testing were endorsed at a higher rate relative to limitations and risks; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
61
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(71 citation statements)
references
References 26 publications
7
61
2
Order By: Relevance
“…This is in contrast to studies of African American women, which have found that cancer-specific fatalism is higher among those considering BRCA testing [72] and those who participate in GCRA and receive BRCA test results [73]. In our study, cancer-specific fatalism was lower in individuals who were more self-efficacious.…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast to studies of African American women, which have found that cancer-specific fatalism is higher among those considering BRCA testing [72] and those who participate in GCRA and receive BRCA test results [73]. In our study, cancer-specific fatalism was lower in individuals who were more self-efficacious.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, although about 15% African American women recruited from urban health care facilities believed that genetic testing would be used to show that their ethnic group is inferior, this belief was not reported by Caucasian women (23). However, consistent with prior studies (9,10,19), attitudes about the benefits of genetic testing for smoking susceptibility were endorsed at a higher rate relative to limitations and risks in this study. Despite this, respondents who reported greater perceptions of limitations and risks were less likely to be willing to participate in research on genetics and smoking.…”
Section: Discussionsupporting
confidence: 79%
“…Specifically, respondents were asked ''how likely is it that you would participate in a research study designed to identify genetic risk factors for smoking'' (1 = not at all likely, 4 = very likely). Similar items have been used to evaluate genetic testing intentions for lung cancer susceptibility and other diseases among African American men and women (14,(19)(20)(21).…”
Section: Outcome Variablementioning
confidence: 99%
“…Previous research evaluating the association between risk and perceived benefits and barriers has been inconsistent. Some studies indicate that greater perceived cancer risk is associated with greater perceived barriers to genetic testing and skepticism about the utility of genetic tests (18,19). However, studies examining other health behaviors indicate that greater perceived risk is associated with greater perceived benefits of risk-reducing behaviors (20).…”
Section: Introductionmentioning
confidence: 99%